2009
DOI: 10.4141/cjps08201
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci for paste viscosity characteristics based on the doubled haploid progeny from a cross between two Chinese wheat varieties

Abstract: , J. 2009. Detection of quantitative trait loci for paste viscosity characteristics based on the doubled haploid progeny from a cross between two Chinese wheat varieties. Can. J. Plant Sci. 89: 837Á844. In order to understand the genetic basis of starch pasting viscosity characteristics (the RVA profile, which is produced by the Rapid Visco Analyser) of wheat grain samples, a doubled haploid (DH) population (Huapei 3 )Yumai 57; Yumai 57 is superior to Huapei 3 for RVA profile parameters) and a linkage map cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Epistatic and epistatic × environment interactions are the genetic basis for some traits, as demonstrated in recent QTL mapping studies . In the present study, five pairs of QTLs with an epistatic effect were identified for PV, TV, SB, and PT, accounting for 0.67, 3.35, 2.97, 8.57, and 2.34% of the phenotypic variance, respectively.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Epistatic and epistatic × environment interactions are the genetic basis for some traits, as demonstrated in recent QTL mapping studies . In the present study, five pairs of QTLs with an epistatic effect were identified for PV, TV, SB, and PT, accounting for 0.67, 3.35, 2.97, 8.57, and 2.34% of the phenotypic variance, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Many studies have demonstrated that the QTLs affecting the pasting properties of wheat flour are located on different chromosomes . Deng et al found that the QTLs for RVA parameters were primarily located on chromosomes 1A, 3B, 4A, and 7A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many reports on QTL for quality traits in wheat (Huang et al, 2006 ; McCartney et al, 2006 ; Sun et al, 2008 ; Patil et al, 2009 ; Zhao et al, 2009 ; Tsilo et al, 2011 ; Li et al, 2012 ; Deng et al, 2013 , 2015 ; Zheng et al, 2013 ; Prashant et al, 2015 ), few genes are identified in single QTL analysis. The main reason is that SSR markers previously used in QTL analysis have insufficient density and are often in non-coding regions.…”
Section: Discussionmentioning
confidence: 99%
“…Dough strength and starch pasting characteristics are quantitative traits controlled by multiple genes. Several QTLs for Mixograph (Huang et al, 2006 ; McCartney et al, 2006 ; Patil et al, 2009 ; Tsilo et al, 2011 ; Li et al, 2012 ; Deng et al, 2013 ; Zheng et al, 2013 ; Prashant et al, 2015 ) and RVA parameters (McCartney et al, 2006 ; Sun et al, 2008 ; Zhao et al, 2009 ; Deng et al, 2015 ) were reported using different populations. However, these reports were primarily based on simple sequence repeat (SSR) markers, resulting in relatively large genetic distances defining QTL and markers due to the limited numbers of such markers, which leads to difficulty for gene cloning based on QTL analysis and marker-assisted selection (MAS) in wheat breeding.…”
Section: Introductionmentioning
confidence: 99%